LUZIA, A TEINIAGUÁ DE SANTA FÉ - Gomes, Gínia Maria (Organon, 2012)
This essay consists of an intertextual analysis between Luzia - O tempo eo vento - and the lendary teiniaguá - A Salamanca do Jarau. Erico Veríssimo refershimself to Simões Lopes Neto’s narrative when he nominates “The teiniaguá” thechapter in which Luzia is the main character. This study will try to track some of thefeatures that approaches both characters. Among them we can detach the origin, thephysical aspect and the kind of relationship they have with men.